الزمن الطللي وتجليات الاغتراب الصوفي عند ابن الفارض - زيناي، طارق (جامعة عنابة, 2020)
إذا كان الزمن الطللي في بعده المرجعي المتجلي في الخطابات الشعرية يتأسس بوصفه تقليدا درج عليه الشعراء من خلال علاقته بالحيز المكاني في ماضويته المشعرة بوطأة الزمن، حيث يستحضر في معهود الاستعمال كقيمة سلبية تنعدم فيها مظاهر الحياة، فإن الزمن الطللي في الخطاب الصوفي تنتقل دلالته الحسية إلى قضايا روحية ذات بعد زمني تأخذ دلالات رمزية مغايرة، انفصالا واتصالا؛ انفصالا عن المظاهر الكونية الكثيفة، المحيلة إلى العوالم السفلية، واتصالا ببواطن هذه المظاهر الحاملة للأسرار والحقائق. If the Al-Talal time in its referential interval which lies in poetic speeches is based as a custom for poets, through its relationship with spatial space in its poetic past with the time when its use is like a negative VA without any manifestations of life, then, the sensual significance of the Atalalic time in the Mystical Discourse (Sufism) transform into spiritual questions with a temporal dimension that take different symbolic connotations, in separation from dense cosmic manifestations and in connection to the interior of these manifestations that carry secrets and truths.
Keywords: ابن الفارض، شرف الدين عمر، ت. 1234 م. -- الشعر الصوفي -- الشعر العربي -- الاغتراب الصوفي